Public Understanding and Perception about Basic Economics and Finance: A Study on Financial Literacy and Decision-Making - Upadhyaya, Yadav Mani; Budhathoki, Prem Bahadur (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This study assesses the level of familiarity with economic terms, the interest in their practical application, and perceptions of economic education methods among individuals in Nepal. The required data were collected from 406 respondents across Nepal through structured questionnaires and qualitative feedback. This study used regression and structural equation modeling (SEM) to examine the nexus between familiarity, interest, and practical understanding of economics/finance. The results show moderate familiarity with basic economic concepts; however, significant gaps prevail, especially among lower-income and less-educated groups. Furthermore, public opinion regarding interest in using economic terms is high (81%), but confidence in understanding complex topics is low. The outcome also demonstrated that the management of personal finance and engagement in economic discussions showed stronger agreement as compared to the national development issues. Familiarity with basic topics positively impacts attitudes toward economic learning. Similarly, personal economic literacy strongly influences societal awareness. The findings of this study concluded that basic education about economics/finance is needed, particularly among marginalized communities, with simplified resources and teaching methods, to bridge knowledge gaps. Increasing practical knowledge about economics/finance can help individuals make informed decisions and contribute to societal progress.